Intensity and Learning Outcomes in the Treatment of Children With Autism Spectrum Disorder. (March 2017) - Linstead, Erik; Dixon, Dennis R.; French, Ryan; Granpeesheh, Doreen; Adams, Hilary; German, Rene; Powell, Alva; Stevens, Elizabeth; Tarbox, Jonathan; Kornack, Julie
Ample research has shown that intensive applied behavior analysis (ABA) treatment produces robust outcomes for individuals with autism spectrum disorder (ASD); however, little is known about the relationship between treatment intensity and treatment outcomes. The current study was designed to evaluate this relationship. Participants included 726 children, ages 1.5 to 12 years old, receiving community-based behavioral intervention services. Results indicated a strong relationship between treatment intensity and mastery of learning objectives, where higher treatment intensity predicted greater progress. Specifically, 35% of the variance in mastery of learning objectives was accounted for by treatment hours using standard linear regression, and 60% of variance was accounted for using artificial neural networks. These results add to the existing support for higher intensity treatment for children with ASD.